Ethnic acceptance issues amongst sabah and sarawak ethnic groups at sultan idris education university - Bahari K.A.; Suhaili S.; Jamaluddin N.; Umar K.; Zakaria Z. (Blue Eyes Intelligence Engineering and Sciences Publication, 2024)
Indexed by SCOPUS